2021
DOI: 10.4103/jcpc.jcpc_14_20
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Iron Homeostasis Among Nigerians with Chronic Heart Failure

Abstract: Background: Iron deficiency (ID) often coexists with heart failure and has recently become a therapeutic option in its management. Multiple markers are often required to adequately estimate iron status. This study was aimed at describing the status of iron homeostasis among heart failure patients in Nigeria. Materials and Methods: This was a cross-sectional study done at two tertiary centers in Nigeria. One hundred and forty patients with a diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…Other authors have also suggested that AF is more prevalent among men than women (34). This study however found no association of gender with AF in HF subjects, contrary to other reports that have reported such a link (11,14). This may be related to regional variation and relatively small sample size among others.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Other authors have also suggested that AF is more prevalent among men than women (34). This study however found no association of gender with AF in HF subjects, contrary to other reports that have reported such a link (11,14). This may be related to regional variation and relatively small sample size among others.…”
Section: Discussioncontrasting
confidence: 99%
“…The patients were recruited over six months. The full details of the methodology for the Iron Deficiency and ANaemia in Heart Failure (IDAN-HF) study have been published elsewhere (11). The clinical data and other information of enrolled participants were recorded with a data collection form.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies evaluated IV iron, although agents, doses, and frequencies ranged widely. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Intravenous Ironmentioning
confidence: 99%